Impact of Sod Growers’ Grow-in Strategies on the Performance of Zoysiagrass Sod - Olayemi Ojeokun; Jack Fry (Kansas Agricultural Experiment Station Research Reports, 2024)
Cultural practices such as mowing heights or nutrient application at sod growers’ farms can affect zoysiagrass sod performance postharvest and laying. A study conducted with 'Meyer', 'Innovation', and DALZ 1808 involved varying nitrogen levels and mowing heights. The sod, sprigged in June 2021 at the Olathe Horticultural Research and Extension Center (OHREC), was harvested in the summer of 2023 and laid at OHREC and Rocky Ford Turfgrass Research Center (RFTRC), Manhattan, Kansas. Results showed that aerification before sodding reduced the normalized difference vegetation index (NDVI) and quality of DALZ 1808 but not Meyer and Innovation. RFTRC has a Chase silty clay loam with a pH of 7.1 while OHREC has an Oska-Martin silty clay loam with a pH of 6.0. Meyer developed an extended root length than Innovation and 1808 in Manhattan, after nine days of sodding and a lower mowing height at grow-in increased the root numbers in Olathe. After a drought period, Meyer was significantly stressed in Olathe compared to Innovation and DALZ 1808. Overall, aerification may adversely affect some zoysiagrass genotypes and growers’ practices may impact the rooting and turf quality of the sod.
Keywords: sod; aerification; mowing height; fertilization; turf quality and NDVI